Atypical functional hierarchy contributed to the tinnitus symptoms in patients with vestibular schwannoma - Lin, Jiaji; You, Na; Li, Xiaolong; Huang, Jiayu; Lu, Haoxuan; Hu, Jianxing; Zhang, Jun; Lou, Xin (Frontiers in Neuroscience, 2023)
Objective: Tinnitus is frequently found in patients with vestibular schwannoma (VS), but its underlying mechanisms are currently unclear. Methods: Both preoperative (VS_pre) and postoperative (VS_post) functional MR images were collected from 32 unilateral VS patients and matched healthy controls (HCs). Connectome gradients were generated for identification of altered regions and perturbed gradient distances. Tinnitus measurements were conducted for predictive analysis with neuroimaging-genetic integration analysis. Results: There were 56.25% of preoperative patients and 65.63% of postoperative patients suffering from ipsilateral tinnitus respectively. No relevant factors were identified including basic demographics info, hearing performances, tumor features and surgery approaches. Functional gradient analysis confirmed atypical functional features of visual areas in VS_pre were rescued after tumor resection, while the gradient performance in the postcentral gyrus continue to maintain (VS_post vs. HC: P = 0.016). The gradient features of postcentral gyrus were not only significantly decreased in tinnitus patients (PFDR = 0.022), but also significantly correlated with tinnitus handicap inventory (THI) score (r = -0.30, P = 0.013), THI level (r = -0.31, P = 0.010), and visual analog scale (VAS) rating (r = -0.31, P = 0.0093), which could be used to predict VAS rating in linear model. Neuropathophysiological features linked to tinnitus gradient framework were linked to Ribosome dys-function and oxidative phosphorylation. Conclusions: Altered functional plasticity in the central nervous system is involved in the maintenance of VS tinnitus.